Alternância de hospedeiros de criação e efeito de bioinseticidas no parasitismo de Trichogramma pretiosum em ovos de Plutella xylostella - Figueroa, Claudio Antonio Salas [UNESP] (2015)
Species of the Trichogramma Westwood (Hymenoptera: Trichogrammatidae) genus are used to control Lepidoptera pests in many crops of economic importance, however, little is known about their parental or breeding hosts; this may be a limiting factor in the search and localization of the target pest in field conditions. In this perspective, the purpose of the present study was to breed the parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) alternating the breeding hosts Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) and target, Plutella xylostella Linnaeus (Lepidoptera: Plutellidae), so as to assess the influence of hosts alternation in the acceptance and preference. To this end T. pretiosum was bred for successive generations in the alternate host C. cephalonica and later on in the natural host, P. xylostella. The number of parasited eggs and the emergence percentage per host was assessed in each generation. The preference towards both hosts was also determined in each generation, using experimental sands, with and without choice possibilities. In this way it was possible to determine the number of generations required for the parasitoid to increase its acceptance of the natural host P. xylostella, an unpredictable factor for the success of biological control of this important pest; thus setting the basis to carry out improvements in the mass breeding systems of these parasitoids. The effect of products based on Bacillus thuringiensis Berliner on the parasitic performance of T. pretiosum upon P. xylostella eggs was also studied. The evaluated T. pretiosum Tp8 strain was recorded in the preference tests with host's alternation and in the free choice tests, showing a preference towards the C. cephalonica host. However, when P. xylostella was offered singly with no choice possibilities, the parasitism and emergence levels obtained were,66% and 64% respectively, thus showing that the conditioning towards ...